2021
DOI: 10.1111/1442-1984.12354
|View full text |Cite
|
Sign up to set email alerts
|

The pollination of the gynomonoecious Bdallophytum oxylepis (Cytinaceae, Malvales)

Abstract: Bdallophytum oxylepis is a rare and endemic species belonging to the Cytinaceae family, a root holoparasitic plant in which most resources are allocated to attracting pollinators. This species is gynomonoecious with intraindividual variation in flower size and sex. Moreover, the flowers exhibit sapromyophilous traits, as do other species of Bdallophytum. Firstly, this study aimed to determine whether all floral morphs can form seeds and be pollen donors (in the case of bisexual flowers). Secondly, as this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Previous estimates of the crown age of Cytinaceae, 66.6-60.9 Myr according to Hernández-Gutiérrez and Magallón (2019), correspond to the KPB, which, by driving much of plant biodiversity to extinction, may have triggered the diversification of new angiosperm life histories such as endophytic parasitism (Naumann et al, 2013). In the nuclear tree (Figure 2), the early divergence of the Malagasy lineage of Cytinus from an ancestor that probably inhabited tropical African biomes is consistent with the tropical deciduous and evergreen forests occupied by Bdallophytum and Muntingia in America (Alvarado-Cárdenas, 2009;Fleming et al, 1985;Rios-Carrasco et al, 2022;Rios-Carrasco & Vazquez-Santana, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…Previous estimates of the crown age of Cytinaceae, 66.6-60.9 Myr according to Hernández-Gutiérrez and Magallón (2019), correspond to the KPB, which, by driving much of plant biodiversity to extinction, may have triggered the diversification of new angiosperm life histories such as endophytic parasitism (Naumann et al, 2013). In the nuclear tree (Figure 2), the early divergence of the Malagasy lineage of Cytinus from an ancestor that probably inhabited tropical African biomes is consistent with the tropical deciduous and evergreen forests occupied by Bdallophytum and Muntingia in America (Alvarado-Cárdenas, 2009;Fleming et al, 1985;Rios-Carrasco et al, 2022;Rios-Carrasco & Vazquez-Santana, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…Sapromyophily has been highly reported for different non-parasitic angiosperm species such as Araceae, Apocynaceae, Aristolochiaceae, Orchidaceae, and others (Johnson 2016 ; Jürgens and Shuttleworth 2015 ), but as we mentioned before, the sapromyophilous endoparasites have received less attention. In that sense, in addition to Rafflesiaceae, other endoparasitic sapromyophilous species exist, such as those of the genus Bdallophytum of the Cytinaceae family (García-Franco and Rico-Gray 1997 ; Rios-Carrasco et al 2022a , 2022b ). Pollination studies confirmed that B. americanum (formerly B. bambusarum ) is pollinated by carrion flies (García-Franco and Rico-Gray 1997 ), while B. andrieuxii and B. oxylepis are pollinated by butterflies and stingless bees respectively, indicating that carrion behaviour is not exclusive to carrion flies (Rios-Carrasco et al 2022a , 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, in addition to Rafflesiaceae, other endoparasitic sapromyophilous species exist, such as those of the genus Bdallophytum of the Cytinaceae family (García-Franco and Rico-Gray 1997 ; Rios-Carrasco et al 2022a , 2022b ). Pollination studies confirmed that B. americanum (formerly B. bambusarum ) is pollinated by carrion flies (García-Franco and Rico-Gray 1997 ), while B. andrieuxii and B. oxylepis are pollinated by butterflies and stingless bees respectively, indicating that carrion behaviour is not exclusive to carrion flies (Rios-Carrasco et al 2022a , 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the nectar of B. americanum and C. hypocistis pistillate flowers has higher sugar concentrations than their staminate counterparts. The exception is B. oxylepis , of which the flowers do not produce nectar but offer pollen to stingless bees as pollinators (Rios‐Carrasco et al, 2021). Furthermore, Mitrastemon yamamotoi (Mitrastemonaceae) flowers produce abundant nectar, and then a variety of pollinators actively forage the flowers (Suetsugu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These plants have various reproductive strategies; for example, parasitic plants have various sexual systems, such as androdioecy, dioecy, hermaphroditism, monoecy, and gynomonoecy, and most are animal‐pollinated. A wide range of pollinators have been recorded, from vertebrates to insects (Bellot & Renner, 2013; Heide‐Jørgensen, 2008; Rios‐Carrasco et al, 2021). However, ecological data on parasitic plant reproduction are scarce because such data take longer to document than genetic and molecular data (Bellot & Renner, 2013).…”
Section: Introductionmentioning
confidence: 99%